Identification of Gene Related to Hard Bunch Phenotype in Oil Palm (Elaeis guineensis Jacq.) - ,, Roberdi; ,, Sobir; Yahya, Sudirman; Toruan-Mathius, Nurita; Liwang, Tony (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2015)
ABSTRACTMolecular genetic analysis of hard bunch phenomenon in oil palm was done in order to elucidate the role of genetic factor underlying hard bunch in oil palm plantation. The aim of this study was to identify the AFLP primer combination that co-segregates with hard bunch phenotype related gene in oil palm. Molecular analysis was done by bulk segregant analysis approach. DNA was isolated from leaves of the normal and hard bunch palm. DNA from ten individual palms from each category were pooled and used as a template. A total of 56 AFLP primer combinations were selected for selection of polymorphic primer, and as a result it was found that 22 AFLP primer combinations (39.28%) were polymorphic. A total of 48 individual of palm DNA containing 24 individual for each group were further genotyped by those 22 polymorphic markers. Of these, one AFLP primer combination (E-ACC/M-CTG) was obtained as a co-segregated marker that distinguished the hard bunch DNA from the normal one. Based on the analysis of the target sequence aligned to the oil palm DNA sequences available in database, we found that our sequence has similarity with Ty-1 copia retrotransposon. This sequence distribute in all 16 linkage group of oil palm genome.Keywords: abnormal fruits, AFLP, oil palm, Ty-1 copia retrotransposon